AN UNUSUAL OCCURRENCE OF HYPOPITUITARISM IN MOSAIC TURNER SYNDROME: A CASE REPORT - Ravindra, Shruthi; Thirupathe, Sunanda; Sarathi, Vijaya; K, Dileep Kumar (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Turner syndrome (TS), the most common chromosomal anomaly in females, is characterized by short stature, hypergonadotropic hypogonadism and various congenital malformations. We report a case of concomitant multiple pituitary hormone deficiencies and gonadal dysgenesis. CASE An 18-year-old female was referred to our hospital for evaluation of short stature and primary amenorrhoea. Examination revealed severe short stature (height 131 cm, -4.2 SD), weight 27 kg with a BMI 15.7 kg/m2, high arched palate, hypertelorism, increased facial naevi, camptodactyly with wide sandal gap. She had a female phenotype with female external genitalia and Tanner stage 1 for both breast and pubic hair development. Hormonal evaluation showed growth hormone (GH) deficiency and relative adrenal insufficiency after the clonidine and ACTH stimulation tests, respectively; low basal gonadotropin levels; low- normal prolactin levels; and intact thyroid axis. Abdominal ultrasonography showed pre-pubertal uterine and ovarian dimensions. Pituitary MRI revealed features suggestive of pituitary hypoplasia. Cytogenetic analysis pattern showed mosaic TS: mos 46,X,del(X)(q24)[17]/45,X[13]. The patient was diagnosed with concomitant hypopituitarism and mosaic TS. She was started on hydrocortisone and sex hormone replacement therapy, as financial constraints affected the decision on recombinant human GH therapy. CONCLUSION Mosaic TS with pituitary hormone deficiency is a very rare occurrence, probably the first case report from Indian literature. Combined gonadotropin, corticotropin and somatotropin deficiencies were previously not reported. In multiple pituitary hormone deficiencies, karyotyping should be performed even in presence of the slightest stigmata of TS.